A review of electrogenerated chemiluminescent biosensors for assays in biological matrices. (October 2016) - Gross, Erin M; Maddipati, Sai Sujana; Snyder, Sarah M
Electrogenerated chemiluminescence (ECL) is the production of light via electron transfer reactions between electrochemically produced reagents. ECL-based biosensors use specific biological interactions to recognize an analyte and produce a luminescent signal. Biosensors fabricated with novel biorecognition species have increased the number of analytes detected. Some of these analytes include peptides, cells, enzymes and nucleic acids. ECL biosensors are selective, simple, sensitive and have low detection limits. Traditional methods use ruthenium complexes or luminol to generate ECL. Nanomaterials can be incorporated into ECL biosensors to improve efficiency, but also represent a new class of ECL emitters. This article reviews the application of ruthenium complex, luminol and nanomaterial-based ECL biosensors to making measurements in biological matrices over the past 4 years.